2023
DOI: 10.1037/sgd0000555
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of psychological distress, employment, and housing among transgender and gender diverse individuals during the COVID-19 pandemic.

Abstract: Transgender and gender diverse (TGD) individuals are faced with various societal factors that contribute to health disparities. As COVID-19 spreads, health disparities that existed prior to the pandemic have become exacerbated. The current study aims to address factors that may be negatively impacting TGD individuals during the COVID-19 pandemic by exploring their experiences related to symptoms of depression, symptoms of anxiety, employment, and housing. TGD participants (N = 342) were recruited from an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…Findings evidence that although most of LTNB participants were negatively impacted by the COVID-19 pandemic in multiple aspects of their lives, those living in Puerto Rico experienced these differently when compared to those in mainland US. Similar to other studies, mental health challenges were identified, including increased worry about contracting COVID-19 [5,15]. Moreover, feelings of stress, anxiety, sadness, and hopelessness were prevalent among the sample regarding the current pandemic.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Findings evidence that although most of LTNB participants were negatively impacted by the COVID-19 pandemic in multiple aspects of their lives, those living in Puerto Rico experienced these differently when compared to those in mainland US. Similar to other studies, mental health challenges were identified, including increased worry about contracting COVID-19 [5,15]. Moreover, feelings of stress, anxiety, sadness, and hopelessness were prevalent among the sample regarding the current pandemic.…”
Section: Discussionsupporting
confidence: 77%
“…Evidence shows the particularly detrimental psychosocial and emotional consequences of the COVID-19 pandemic for TNB, including increased unemployment and lack of secure housing [15], increased anxiety and depression [16], unmet mental health needs [17], increased use of alcohol [18], and higher prevalence of suicide thoughts [19,20]. Some of these disparities can be explained by the social determinants of health influencing the health status of minoritized TNB individuals [15,21]. Nevertheless, little is known about their impact among TNB with multiple marginalized intersecting identities, such as Latinx trans and non-binary individuals (LTNB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation